2012
DOI: 10.1590/s1519-69842012000300015
|View full text |Cite
|
Sign up to set email alerts
|

Structure of aquatic vegetation of a large lake, western border of the Brazilian Pantanal

Abstract: Studies on Neotropical aquatic macrophytes have increased in recent decades, however species richness in wetlands of South America is far from being fully known. In addition, studies having an ecological approach are scarce in the Pantanal. Rapid assessments are essential for gaining knowledge of the biodiversity in the region. This study was performed in five sites of the Baía do Castelo, the western border of the Brazilian Pantanal, which included wild-rice patches, floating mats and floating meadows. At eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
(64 reference statements)
0
10
0
1
Order By: Relevance
“…The ecological role of fire in SDTF, growing primarily to the west of LLG today, in the Chiquitanía region of eastern Bolivia, remains uncertain due to the paucity of suitable palaeo archives (lake and bog sediments) in this landscape. North and east of LLG are the Pantanal tropical wetlands, which are a mosaic landscape dominated by seasonally flooded savannas and riparian gallery forests, and shaped by regularly occurring floods and occasional wildfires [9,18,37].…”
Section: Results and Interpretationmentioning
confidence: 99%
“…The ecological role of fire in SDTF, growing primarily to the west of LLG today, in the Chiquitanía region of eastern Bolivia, remains uncertain due to the paucity of suitable palaeo archives (lake and bog sediments) in this landscape. North and east of LLG are the Pantanal tropical wetlands, which are a mosaic landscape dominated by seasonally flooded savannas and riparian gallery forests, and shaped by regularly occurring floods and occasional wildfires [9,18,37].…”
Section: Results and Interpretationmentioning
confidence: 99%
“…June-11 stages of succession (Pivari et al, 2008;Cunha et al, 2012). Most of them persisted after fire, with a relatively fast restart of succession, some of them from buried regenerative structures and others from soil seed bank.…”
Section: May-11mentioning
confidence: 99%
“…At the generic level, species richness varies among studies. Besides the common predominance of some genera of Cyperaceae (Cyperus, Eleocharis and Rhynchospora) (Lima et al 2011, Meyer & Franceschinelli 2011, Rocha et al 2015, several reports showed an elevated species richness of Ludwigia (Onagraceae) (Pivari et al 2011, Cunha et al 2012. Ludwigia is among the most represented genera of aquatic plants in the Pantanal (Pott et al 2011) and was also cited by Pivari et al (2008) as the most representative genus for floating meadows in the Pantanal in the sub-regions of Abobral and Miranda.…”
Section: Discussionmentioning
confidence: 99%